GUIDANCE AND COUNSELING STUDENTS’ PROFILE OF CAREER MATURITY: REVIEWING FROM ETHICAL DIFFERENCES - Vira Afriyati; Anna Ayu Herawati (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2022)
The aim of this article is to examine the career maturity profile of University of Bengkulu Guidance and Counselling student. This research is a census study, all the population is used as a sample. There are nine tribes in this study consisting of Serawai, Javanese, Rejang, Minang, Palembang and Lintang, Basemah, Batak, Lembak and Bengkulu, and others. A career maturity questionnaire was employed as the instrument. The descriptive statistical analysis and the Kruskal Wallis Statistical Test were used to analyse the data. The results showed that there was no significant difference between the career maturity profiles of students from different ethnic backgrounds. The results of this study can be used as a basis for developing student career development programs.